2013
DOI: 10.1504/ijlr.2013.054188
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in radioactive waste management: a global perspective

Abstract: The present study is aimed at analysing the growth of literature on radioactive waste management. International Nuclear Information System (INIS) database is used as a data source to analyse the focused areas of this field for the period 1970-2011. Journal Citation Report-2010 is used for eliciting information related to journal impact factors. The database contained a total of 101,419 publications covered by all the channels of communication during the period. The study analyses the broad features focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The research adds to the notion of input waste by using TISM to construct a hierarchical link between waste management components. TISM is frequently used in the management and technical domains to model conceptual frameworks (Bala et al, 2020;Kademani et al, 2013;Srivastava, 2013). The paper aims to identify essential waste management components and construct a model that depicts the hierarchical connection between them.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The research adds to the notion of input waste by using TISM to construct a hierarchical link between waste management components. TISM is frequently used in the management and technical domains to model conceptual frameworks (Bala et al, 2020;Kademani et al, 2013;Srivastava, 2013). The paper aims to identify essential waste management components and construct a model that depicts the hierarchical connection between them.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…In particular, in order to have an intuitively clearer representation with a mathematical meaning (see, Eqs. [1][2][3][4][5][6][7][8]), the authors proposed to use the graphical metric based on the 'square surface areas' which represents subsurface structural boundary for the documents published by 'A' or 'B' systems, and the co-publication produced together.…”
Section: A-bmentioning
confidence: 99%
“…Many scientometrics studies have been appeared in the literature dealing with the different aspects of scholarly communications [1][2][3][4][5][6][7] . Kademani et al [1] studied the growth and development of world literature on Bhabha Scattering by using three different databases 'International Nuclear Information System' (INIS), Science Citation Index, and INSPEC and found that a total of 1305 papers were published by the scientists in the field Bhabha Scattering during 1969-2008; and there were 47 countries involved in the research in this field where Germany was the top producing country with 421 papers followed by the USA with 420 papers, Italy with 293 papers, and Switzerland with 263 papers.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Many scientometric studies have appeared in the literature to focus on the performance of nuclear science and technology. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Scientometric studies are useful in understanding the growth of literature, identifying strengths and weaknesses of a country, organization and an individual in various domains of scientific endeavors. These studies will help the policy makers and science administrators to have better insights in framing science policy and guiding the researchers.…”
Section: Introductionmentioning
confidence: 99%